Determining Cracking of the Post-Drying Paddy Rice - Komar, Nur (Jurnal Teknologi Pertanian, 2001)
Paddy rice is harvested and dried firstly and it is consequently necessary to determine the extent of the cracking. Some drying parameters involving the cracking ratio of the paddy rice are: 1) level of the drying air velocity; 2) the depth of the drying paddy rice pile; 3) temperature of the drying air; 4) the relative humidity; and 5) duration of the drying process. The aims of the study are to 1) determine the relation between the paddy rice cracking ratio, the air velocity and the pile depth, 2) find out the appropriate drying air velocity and the pile depth for drying. From the study result of Yamaguchi et al. (1980) suggested that the cracking ratio caused by thermal stress is highly lower compared to that caused by moisture stress. Water loss of the air velocity 0.4 m s-1 at 1 cm deep was 10.37 % ww after 2 hours of drying. The slower the air velocity andÂ  the deeper the pile, the lower the cracking constant. The lowest cracking constant was at v (air velocity) = 0.2 m/s and 5 cm deep, that is 3.6165936.10-3 minute-1. The cracking ratio-calculation results post-drying is relevant to the experimental results, in which the lowest cracking rate was found at v = 0.2 m/s and 5 cm deep, that is 4%. The cracking size form found in the present study was the circular cracking around the paddy rice. Supplying the drying air velocity of 0.2-0.4 m/s and 1-5 cm deep in this study give the lower final cracking rate that is 4-9%. Â  Keywords: paddy rice, post drying, cracking